2020
DOI: 10.3390/jmse8070493
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hepcidins from Black Rockfish (Sebastes schlegelii) in Iron-Metabolic Function and Bacterial Defense

Abstract: Hepcidin, an antimicrobial peptide produced by the liver, also controls the iron balance and regeneration in vertebrates. Two types of hepcidin (Hamp1 and Hamp2) have been found in the bodies of black rockfish (Sebastes schlegelii). The full-length cDNA of hepcidin was cloned to enable a study of the antibacterial roles of these two hepcidins (Hamp) in black rockfish. The antimicrobial function of recombinant hepcidins was tested both in vitro and in vivo by the synthesis in Escherichia coli of recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…This hepcidin dynamic was already described for other fish species ( 109 112 ). These results are in accordance with other studies that also demonstrated the regulation of hepcidin and ferroportin by inflammatory signals induced by a pathogen ( 108 , 113 116 ).…”
Section: Discussionsupporting
confidence: 93%
“…This hepcidin dynamic was already described for other fish species ( 109 112 ). These results are in accordance with other studies that also demonstrated the regulation of hepcidin and ferroportin by inflammatory signals induced by a pathogen ( 108 , 113 116 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another well-known function of hepcidins is iron regulation. 31 Recently identified hepcidins include the Lc-HepL from large yellow croaker Larimichthys crocea , Hamps from the blackfish Sebastes schlegelii , Pv-hepcidin from the lionfish Pterois volitans etc. , which are effective in killing human or aquatic pathogenic bacteria like Vibrio harveyi and S. aureus , Pseudomonas aeruginosa as well as some parasites.…”
Section: Amps From Different Marine Organismsmentioning
confidence: 99%
“…Specifically, it has only been studied in a few fish species such as Danio rerio (Jiang et al 2017 ), Salmo trutta (Huang et al 2019 ), Oncorhynchus mykiss (Álvarez et al 2014 ), Dicentrarchus labrax (Rodrigues et al 2006 ), or Sparus aurata (Cuesta et al 2008 ). Recently, the expression of hepcidins has also been studied during the larval development of zebrafish (Caccia et al 2017 ) and in some adult fish species [ Ictalurus punctatus (Bao et al 2006 ), Oreochromis mossambicus (Huang et al 2007 ) Cyprinus carpio (Yang et al 2014 ) Sebastes schlegelii (Ma et al 2020 ), and Acrossocheilus fasciatus (Zhu et al 2023 )].…”
Section: Introductionmentioning
confidence: 99%